Nöte und Zäsuren eines modernen Migrantenschicksals – der deutsch-polnische Grenzgänger Artur Becker und sein Roman ,Das Herz von Chopin’ - Krauze-Olejniczak, Alicja (Studia Germanica Posnaniensia, 2013)
The following article aims at presenting the main emigration-related interpretative aspects of Becker’s prose and attempts to put them in the context of the post-colonial theories. The characters created by Artur Becker, who calls himself a “Polish writer of German language”, roam continually between the old and the new fatherland and struggle with the feeling of not belonging to any of these worlds. The experience of alienation in foreign country stems from a “transition” in a double sense: on the one side a physical change of the place of residence to Germany which means crossing the “mystical” frontier between the East and the West and on the other a fruitful caesura: the crisis of the identity leads the protagonists of Becker to the conclusion that this hybridity constitutes an intellectual potential and an existential skill. In the introduction, the foundations of the Postcolonial Theories will be outlined, with the emphasis on the concept of Homi Bhabha which postulates that the fluidity of identity forming in a symbolic “third space”, enables the cultural hybridity. Subsequently, after a short presentation of the characters and the work of Artur Becker, the research will focus on the novel Das Herz von Chopin (Chopin’s Heart), in which the main character – a financially successful car dealer who emigrated from the communistic Poland to Germany almost 20 years ago while being internally conflicted begins to explore a zone betwixt-and-between to find his own way to happiness.